Development of Emergency Notification System for Passenger Lift using IoT - Mohd Faizal, Muhammad Aliff Iqmal; Muhammad Hazli Mazlan (Evolution in Electrical and Electronic Engineering, 2023)
This work aims to develop a highly efficient and reliable notification system that promptly alerts the emergency response team in the event of a passenger elevator failure, addressing the need to improve the safety and well-being of individuals trapped in elevators. The main research objectives focus on minimizing response time for the responsible party and engaging relevant stakeholders through the utilization of advanced components such as ESP8266, GSM Module, Arduino, and Blynk software. The study incorporates these materials and follows standard procedures to ensure the system's functionality. Key findings indicate the system's effectiveness with average notification times of 5.91 seconds for email, 1.35 seconds for phone, and 9.03 seconds for SMS notifications, regardless of internet connectivity. The discussion emphasizes the successful reduction in response time and suggests future work could involve further system optimization and integration with additional emergency response mechanisms.